Compensation and Work Spirit: Does Work Motivation Mediate the Impact? - Ni Wayan Regita Prita Mahardewi; I Gusti Ayu Manuati Dewi (International Journal of Asian Business and Management, 2024)
Village credit union (Lembaga Perkreditan Desa/LPD) is a kind of financial institutions in Bali Province-Indonesia which is established by the community. In carrying out work, employees will indeed always be in the spirit of work in endeavor to provide maximum results to the company. High morale needs to be maintained by employees working together to achieve company goals. Of course, this is an advantage for the company because it has quality resources to achieve its goals. This study aimed to analyze the effect of compensation on work spirit with work motivation as a mediator for employees at an LPD located in Kesiman Municipality. The sample of this study was 61 employees using saturated sampling. Data was collected by conducting interviews and distributing questionnaires. Hypothesis was tested by implementing Path Analysis. The findings show that compensation has a positive and significant effect on work spirit, compensation has a positive and significant effect on work motivation, work motivation has a positive and significant effect on work spirit, and work motivation mediates the effect of compensation on work spirit. Implication of this study is the management of LPD is advised to increase the work spirit of its employees by paying attention to compensation and work motivation of its employee